PENGEMBANGAN E-MODUL CANVA TEMA 7 SUBTEMA 2 PADA MATA PELAJARAN IPA MATERI MACAM-MACAM GAYA UNTUK SISWA KELAS IV - Alfanti Shindika Sari Alfa; Lina Novita; Ade Wijaya (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Canva's E-module learning can make learning more optimal because students have repeated access to learning materials that can be accessed anywhere. This study aims to determine the feasibility of e-module teaching materials on the theme 7 The Beauty of Diversity in My Country, the sub-theme The Beauty of Cultural Diversity of My Country for class IV SD. The method used in this study was research and development (Analysis, Design, Development, Implementation, Evaluation). starting with gathering information on needs, making e-module designs, expert validation, revising products, after that limited product trials and evaluations. The research results from the validation of linguists, media experts, and material experts get an overall average percentage of 93% which indicates that Canva's e-module is “Very Decent”. At the limited trial stage, the students' response to the Canva e-module "Very Good" was obtained by obtaining an overall average percentage of 86%. Based on the results of the research from expert validation and student responses, it can be concluded that the development of the Canva e-module theme 7 sub-theme 2 in the Natural Sciences subject matter of various styles for grade IV students is very feasible and well used in the learning process, interesting, interactive, and practical.